Rh(III)-Catalyzed Olefination and Alkylation of Arenes with Maleimides: A Tunable Strategy for C(sp2)–H Functionalization - Zhang, Wenjie; Liu, Xueyan; Tian, Zhenfeng; Li, Hongji (Synthesis, 2021)
We herein report a new nitrogen-directed Rh(III)-catalyzed C(sp2)–H bond functionalization of N-nitrosoanilines and azoxybenzenes with maleimides as a coupling partner, in which the olefination/alkylation process can be finely controlled at room temperature by variation of the reaction conditions. This method shows excellent functional group tolerance, and presents a mild access to the resulting olefination/alkylation products in moderate to good yields.
Keywords: rhodium catalysis; nitrosoanilines; azoxybenzenes; olefination; alkylation